Intraoperative Ultrasound: A Tool to Support Tissue-Sparing Curative Pancreatic Resection in Focal Congenital Hyperinsulinism - Bendix, Julie; Laursen, Mette G.; Mortensen, Michael B.; Melikian, Maria; Globa, Evgenia; Detlefsen, Sönke; Rasmussen, Lars; Petersen, Henrik; Brusgaard, Klaus; Christesen, Henrik T. (Frontiers in Endocrinology, 2018)
Background: Focal congenital hyperinsulinism (CHI) may be cured by resection of the focal, but often non-palpable, pancreatic lesion. The surgical challenge is to minimise removal of normal pancreatic tissue. Aim: To evaluate the results of intraoperative ultrasound-guided, tissue-sparing pancreatic resection in CHI patients at an international expert centre. Methods: Retrospective study of CHI patients treated at Odense University Hospital, Denmark, between January 2010 and March 2017. Results: Of 62 consecutive patients with persistent CHI, 24 (39%) had focal CHI by histology after surgery. All patients had a paternal ABCC8 or KCNJ11 mutation and a focal lesion by 18F-DOPA-PET/CT. Intraoperative ultrasound localised the focal lesion in 16/20 patients (sensitivity 0.80), including one ectopic lesion in the duodenal wall Intraoperative ultrasound showed no focal lesion in 11/11 patients with diffuse CH (specificity 1.0). The positive predictive value for focal histology was 1.0, negative predictive value 0.73. Tissue-sparing pancreatic resection (focal lesion enucleation, local resection of tail or uncinate process) was performed in 67% (n=16). In 11/12 having tissue-sparing resection and intraoperative ultrasound, the location of the focal lesion was exactly identified. Eight patients had resection of the pancreatic head or head/body, four with Roux-en-Y, three with pancreatico-gastrostomy and one without reconstruction. None had severe complications to surgery. Cure of hypoglycaemia was seen in all patients after one (n=21) or two (n=3) pancreatic resections. Conclusion: In focal CHI, tissue-sparing pancreatic resection was possible in 67%. Intraoperative ultrasound was a helpful supplement to the mandatory use of genetics, preoperative 18F-DOPA-PET/CT and intraoperative frozen sections.